Labour Markets, Trade and Technological Progress: A Meta-Study - Nikos Terzidis; Steven Brakman; Raquel Ortega-Argiles (Center for Economic Studies and ifo Institute (CESifo), 2019)
Technological progress and trade potentially affect wages and employment. Technological progress can make jobs obsolete and trade can increase unemployment in import competing sectors. Empirical evidence suggests that both causes are important to explain recent labour market developments in many OECD countries. Both causes are often mentioned in tandem, but the relative contribution of each cause is less clear. This study presents a meta-analysis to shed light on the relative contribution of technological progress and trade in recent labour market developments and allows us to identify the winners and losers of automation and globalization. Using a sample of 77 studies and 1158 estimates, we find that both effects are important. Automation is beneficial at the firm level, and is more likely to displace low-skilled employment. Trade is more likely to benefit high-skilled employment and affects industry negatively. Somewhat surprisingly, given the consensus in the literature, automation has a positive effect for estimates considering the period before 1995, and trade a negative effect. We also find some evidence of publication biases.
Keywords: F23; J31; J63; O11; 330; labour markets; technological progress; trade; meta-study